Cardiovascular and vegetative adaptation of the body of cadets of the Institute of Civil Aviation to different types of locomotor motion activity - A. I. Ryazantsev; E. K. Grebennikov; I. N. Grebennikova; O. V. Sorokin; M. A. Subotyalov (Сибирский научный медицинский журнал, 2024)
The aim of study was to investigate the indicators of cardiovascular and autonomic adaptation of cadets of the Institute of Civil Aviation to different types of locomotor motion activity. Material and methods. Heart rate, blood pressure, cardiovascular indices were assessed in 96 healthy cadets divided into four groups according to the type of their locomotor motion activity. The study also analyzed Baevsky’s indices. Results and its discussion. The analysis of cardiovascular indicators and indicators of heart rate variability both in the background state and in response to an active orthostatic test revealed an increase in the adaptive reserve and heart rate variability in the series «not engaged» – «self-exercising» – «game sports» – «cyclical sports». It has been established that cadets involved in cyclic sports have greater parasympathetic activity and its influence on the heart rate both at rest and in response to orthostatic load, which reflects a deeper degree of their adaptation to physical and educational load, based on structural changes in cells of the cardiovascular, nervous and endocrine systems. Apparently, the data obtained indicate the manifestation of a general strategy of structural and functional restructuring of the body’s regulatory systems, aimed at the formation of optimal compensatory and adaptive changes in hemodynamics.